2018
DOI: 10.1111/gcb.14501
|View full text |Cite
|
Sign up to set email alerts
|

Functional reorganization of marine fish nurseries under climate warming

Abstract: While climate change is rapidly impacting marine species and ecosystems worldwide, the effects of climate warming on coastal fish nurseries have received little attention despite nurseries’ fundamental roles in recruitment and population replenishment. Here, we used a 26‐year time series (1987–2012) of fish monitoring in the Bay of Somme, a nursery in the Eastern English Channel (EEC), to examine the impacts of environmental and human drivers on the spatial and temporal dynamics of fish functional structure du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 116 publications
1
36
1
Order By: Relevance
“…As a global warming hotspot (Hobday & Pecl, ), the North Sea has been heavily impacted by temperature rise over the last few decades, with documented increases in fishes with small body sizes and fast life history strategies, particularly pelagic species (Beukhof et al, ; McLean, Mouillot, Lindegren, et al, ; Pecuchet et al, ; Simpson et al, ). Previous studies have suggested that such species can rapidly track environmental changes due to short generation times, fast population turnover, and by producing small, pelagic larvae with high dispersal rates (McLean, Mouillot, Goascoz, Schlaich, & Auber, ; Rijnsdorp et al, ). These species are further believed to have greater long‐term adaptive and evolutionary capacity given their quick population turnover and greater potential for rapid natural selection (Rijnsdorp et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a global warming hotspot (Hobday & Pecl, ), the North Sea has been heavily impacted by temperature rise over the last few decades, with documented increases in fishes with small body sizes and fast life history strategies, particularly pelagic species (Beukhof et al, ; McLean, Mouillot, Lindegren, et al, ; Pecuchet et al, ; Simpson et al, ). Previous studies have suggested that such species can rapidly track environmental changes due to short generation times, fast population turnover, and by producing small, pelagic larvae with high dispersal rates (McLean, Mouillot, Goascoz, Schlaich, & Auber, ; Rijnsdorp et al, ). These species are further believed to have greater long‐term adaptive and evolutionary capacity given their quick population turnover and greater potential for rapid natural selection (Rijnsdorp et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Panels (b) and (d) show temporal changes in taxonomic (Bray-Curtis) and trait-based (modified Rao's Quadratic Entropy) beta diversity for the entire North Sea. Dotted lines indicate best fits from linear regressions and R 2 values are indicated in the upper left corner of each plot such species can rapidly track environmental changes due to short generation times, fast population turnover, and by producing small, pelagic larvae with high dispersal rates (McLean, Mouillot, Goascoz, Schlaich, & Auber, 2019;Rijnsdorp et al, 2009). These species are further believed to have greater long-term adaptive and evolutionary capacity given their quick population turnover and greater potential for rapid natural selection (Rijnsdorp et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Global warming exerts considerable effects on the marine ecosystems (Hoegh-Guldberg and Bruno, 2010;Kersting, 2016), which are affecting fish assemblages (e.g., Anacleto et al, 2018;Carozza et al, 2019;McLean et al, 2019), and the global fisheries that exploit them (Phillips and Pérez-Ramírez, 2017;Barange et al, 2018). It is plausible that recreational fisheries will be affected in a similar way to commercial fisheries (especially SSF), so response to global warming may be comparable in some cases (Townhill et al, 2019).…”
Section: Recommendations To Improve Researchmentioning
confidence: 99%
“…Given that more than a half of small fish individuals tend to remain in a vulnerable size during their entire lives (Goatley & Bellwood, ), changes in shelter availability due to a functional reorganization of coral assemblages can potentially impact adult populations of these vulnerable and dominant small‐bodied fishes. Recently, marine fish communities underwent a climate‐driven functional switch from fast to slow life‐history species dominance (McLean, Mouillot, Goascoz, Schlaich, & Auber, ). In coral reefs, shifts from species with small body size and fast lifespan to large‐bodied and slow life‐history dominance can disrupt food chains (Hempson, Graham, MacNeil, Hoey, & Almany, ) and severely decrease ecosystem productivity (Brandl et al, ).…”
Section: Discussionmentioning
confidence: 99%